-100=12t-4
-100-12t+4=0
-96-12t=0
-96=12t
-8=t
2007-04-29 17:27:15
·
answer #1
·
answered by bootis32 6
·
0⤊
0⤋
t= -8
Move -100 over to the right, and 12t to the left. Your problem becomes -12t=-4+100
-12t=96
divide both sides by -12, thus, t = -8!
Hope that made sense...
2007-04-29 21:46:13
·
answer #2
·
answered by met5473 2
·
0⤊
0⤋
-100=12t-4
-100+4=12t (when a function is shifted to the other side, the quation will be the opposite. therefore, -4 shift to the other side will be +4)
-96/12=t (12t = 12 x t. therefore, when 12 shifted to the other side will be divided)
-8=t
2007-04-29 21:56:54
·
answer #3
·
answered by ad3l3n3 2
·
0⤊
0⤋
-100+4=12t-4+4
-96=12t
-8=t
2007-04-29 21:45:52
·
answer #4
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
-100=12t-4
-100+4=12t
-96=12t
-8=t
2007-04-29 21:49:48
·
answer #5
·
answered by gR3g$ cH!cK 2
·
0⤊
0⤋
-100+4=12t-4+4
-96/12=12t/12
t=-8
2007-04-29 21:45:16
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
-100=12t-4
12t = -100 + 4 = -96
t = -96/12 = 8
2007-04-29 21:43:55
·
answer #7
·
answered by looikk 4
·
1⤊
0⤋
-100=-12t-4
-100+4=-12t-4+4
-96=-12t
t=8
Check:
-100=12(-8)-4
-100=-96-4
-100=-100
2007-04-29 21:43:59
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
-8
2007-04-29 21:43:41
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋